The Illocutionary Acts Found in the Summer I Turned Pretty Film - Marlina, Leni; I Gusti Ayu Vina Widiadnya Putri (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study aimed to analyze the type of speech acts and the classification This text discusses the importance of language as a system of communication between speakers and listeners, and how language is used to convey feelings or share information through speech acts. illocutionary acts refer to the intended meaning of a statement. It is an example of a form of speech act that has been culturally defined and is distinguished by a distinctive illocutionary force. For instance, making promises, giving advice, and making threats are all instances of illocutionary activities. Speech acts theory looks at the pragmatic function of utterances.The theory is premised on the belief that language is used to perform actions. Films are cultural products produced by certain cultures that help individuals of various languages and cultures to communicate with one another. The text presents a literature review that discusses the different types of illocutionary acts and how they are used in human communication. Finally, the text presents the research methodology, findings, and discussion of a study that analyzes the types of illocutionary acts used in the conversations of season 2 of